2012
DOI: 10.1148/radiol.12110986
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Meniscal Extrusion in Knees with or at Risk for Osteoarthritis: The Multicenter Osteoarthritis Study

Abstract: Purpose:To assess the associations of meniscal tears, knee malalignment, cartilage damage, knee effusion, and body mass index with meniscal extrusion. Materials and Methods:The Multicenter Osteoarthritis study is an observational study of individuals who have or are at risk for knee osteoarthritis (OA). The HIPAA-compliant protocol was approved by the institutional review boards of all participating centers, and written informed consent was obtained from all patients. All subjects with available baseline knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
180
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(197 citation statements)
references
References 47 publications
(72 reference statements)
15
180
0
2
Order By: Relevance
“…The higher frequency for both menisci seen in this study could be explained by the higher sample size of the study and the included population having osteoarthritis or risk factor for it. (20) Our study showed a higher frequency of meniscal extrusion in females, occurring in 39.1% of the female population and 23.1% in the male. This was also shown in other studies.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The higher frequency for both menisci seen in this study could be explained by the higher sample size of the study and the included population having osteoarthritis or risk factor for it. (20) Our study showed a higher frequency of meniscal extrusion in females, occurring in 39.1% of the female population and 23.1% in the male. This was also shown in other studies.…”
Section: Discussionsupporting
confidence: 47%
“…This was also shown in other studies. (20,21) Meniscal extrusion was also seen with higher frequency in those patients with a history of trauma (36.8%) in contrast to those without trauma (9.1%).…”
Section: Discussionmentioning
confidence: 97%
“…Among all the other results of univariate analysis, orthostatic MME was found to significantly correlate with the WORMS score of bone spurs (osteophytes). In a large population-based cross-sectional study with over than 1,500 patients [3], clinostatic MME was associated with meniscal tears, varus malalignment, and cartilage damage.…”
Section: Discussionmentioning
confidence: 99%
“…Meniscal pathology in knee osteoarthritis (OA) has been extensively explored [1,2]. In a recent study on a large cohort of 1,527 patients with (or at risk for) knee OA, meniscal extrusion in the medial tibiofemoral (TF) compartment significantly correlated with meniscal tears, varus malalignment, and cartilage damage [3]. In other studies, meniscal extrusion was shown to be an independent predictor of TF cartilage loss [2] and degenerative subchondral bone marrow lesions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The extrusion of any part of a meniscus beyond the tibial plateau during extension and flexion can represent various conditions, including physiologic and pathologic conditions. Substantial meniscal extrusions can suggest meniscal degeneration and tears and are strongly associated with the progression of osteoarthritis [8,9]. Knowledge of the kinematics of the meniscus and joint space is important for understanding the pathogenesis and treatment of meniscal lesions and the development of knee prostheses.…”
Section: Introductionmentioning
confidence: 99%